A noção de crise no campo da saúde mental: saberes e práticas em um Centro de Atenção Psicossocial (CAPS) - Aline Gomes Martins (2013)
The present paper is a qualitative case study. It aims at discussing the crisis notion supporting Psychosocial Attention Centers (CAPS) which offer services of attention to mental health crisis and urgencies. Therefore it were conducted participants observations, interviews to specialized professionals, talks to non specialized professionals and to CAPS users in a Minas Gerais state countryside town. In order to best comprehend the argument, an exploratory bibliographic survey was conducted to investigate the notion of crisis throughout mental health history; from the ideas sustained by classic psychiatry up to the knowledge transmitted by the psychiatric reform. The interviews to the professionals were recorded and transcribed integrally, and analyzed according to the contributions of the content analysis. The interviews analysis allowed the raising of four hypotheses. These hypotheses approach central topics in the respondents speech and were configured in categories of analysis as follows: knowledge ranking, medicalization, protocol overvaluation and crisis conceptions. Each category displays a conflictive issue which intertwines and composes the result for this research. The interviews have shown that most of the professionals feel lost in his duties without knowing what to do or how to act. Such situation can be explained by the hegemony on the medical service which barely leaves room for other fields. Despite the existence of multiple coexisting skills and definitions, it is clear the predominance in the CAPS context of a crisis notion molded by the medical clinic. As the crisis is taken by most of the professionals as a state of intensification of psychiatric symptoms and the patient is evaluated for his behavior, no opportunities are given to other treatments which take in consideration the subjectivity and the complexity of social relations which constitute and keep the crisis. In order to build an effective treatment, it is necessary to break with the hegemony of knowledges and give chances to multiple possibilities of realizing and dealing with the crisis according to the patient demands. It must be primordial the subjective dimension in dealing with the crisis. This treating is built from the relation with the subject, his personal, familiar, professional and emotional records.